Impacts of plant protection products on biodiversity and ecosystem services - Leenhardt, Sophie; Mamy, Laure; Pesce, Stéphane; Sanchez, Wilfried (éditions Quae, 2023)
As part of the Ecophyto II+ plan, INRAE and Ifremer were in 2020 commissioned to conduct a collective scientific assessment of the impacts of plant protection products on biodiversity and ecosystem services. The results, released in May 2022, confirm that plant protection products contaminate all types of terrestrial and aquatic environments, all of their compartments and most of their organisms. Contamination varies according to the distance from the areas where the products are used, principally in agriculture. It causes direct and indirect impacts on ecosystems, notably the decline of populations of terrestrial and aquatic invertebrates and birds, and the loss of ecosystem functions and services. Different measures can help mitigate contamination and its impacts, with varying degrees of effectiveness depending on the particular combination of measures (regulations, conditions of use of products, etc.). This assessment identifies research needs, in particular to improve our understanding of dynamic phenomena in a context of multiple environmental stresses. It aims to characterise and predict impacts and to improve the procedures for assessing the risks associated with the use of plant protection products. This book is targeted at all stakeholders and decision-makers with an interest in the use of plant protection products, whether they are involved in the legal, political, industrial or non-profit sectors, or in research or teaching.